PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP STRES KERJA WARTAWAN PT SERAMBI MEDIA PRESS DI KOTA PADANG - Ahmad Waldyazkia; Nuryanti '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Sreambi Media Press di Kota Padang in order to determine the effect of variable work environment and individual characteristics simultaneously to stress the work of journalists PT. Serambi Media Press di Kota Padang. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT. Serambi Media Press di Kota Padang. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees of 60 people and made in the sample. The analytical method used in this research is multiple linear regression method. From the testing that has been done, simultaneous regression test (Test-F) shows that the work environment and individual characteristics simultaneously significant effect on work stress reporters PT. Serambi Media Press di Kota Padang. From the results of the partial test (t-test) showed that the work environment and individual characteristics significantly influence work stress reporters. The result of the calculation of the coefficient of determination (R2) is equal to 0.744, which means, work environment and individual characteristics together influence the work stress reporters PT. Serambi Media Press di Kota Padang, while the rest influenced by other variables not examined in this study.Keywords: Work Environment, Individual Characteristics and Job Stress